2004
DOI: 10.5194/bgd-1-167-2004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The carbon budget of terrestrial ecosystems at country-scale – a European case study

Abstract: Abstract. We summed estimates of the carbon balance of forests, grasslands, arable lands and peatlands to obtain country-specific estimates of the terrestrial carbon balance during the 1990s. Forests and grasslands were sinking carbon consistently, whereas arable soils were carbon sources in all European countries. Hence, countries dominated by arable lands tended to be losing carbon from their terrestrial ecosystems, whereas forest-dominated countries tended to be sinking carbon. In countries where peatlands … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 9 publications
1
46
0
3
Order By: Relevance
“…Without a more detailed description of the methods used to score supply and demand, the scores themselves can be disputed. For example, the scores they assign for the service "global climate regulation" give the impression that LCC "broad-leaved forest" is in principle able to supply global climate regulation (score 4) at comparable levels to demand on LCC "road and rail networks" (also scored with 4), which is far from realistic (Janssens et al, 2005). In order to adequately compare supply and demand of ES more quantitative methods of scoring are needed.…”
Section: Scoring System For Supply and Demandmentioning
confidence: 99%
“…Without a more detailed description of the methods used to score supply and demand, the scores themselves can be disputed. For example, the scores they assign for the service "global climate regulation" give the impression that LCC "broad-leaved forest" is in principle able to supply global climate regulation (score 4) at comparable levels to demand on LCC "road and rail networks" (also scored with 4), which is far from realistic (Janssens et al, 2005). In order to adequately compare supply and demand of ES more quantitative methods of scoring are needed.…”
Section: Scoring System For Supply and Demandmentioning
confidence: 99%
“…On a local scale, Miglietta et al (2007) found that a European agricultural area could be a net source of carbon even in summer when growth might be expected to be greatest. Across Europe, Janssens et al (2005) found that crop lands are net annual sources of carbon whilst non-crop regions are carbon sinks. Meanwhile, expansion of European forest area, forestry management practices and nitrogen deposition are likely to create a substantial carbon sink (Janssens et al, 2005;Ciais et al, 2005b;Magnani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Across Europe, Janssens et al (2005) found that crop lands are net annual sources of carbon whilst non-crop regions are carbon sinks. Meanwhile, expansion of European forest area, forestry management practices and nitrogen deposition are likely to create a substantial carbon sink (Janssens et al, 2005;Ciais et al, 2005b;Magnani et al, 2007). CO 2 fertilisation (Norby et al, 2005;Ciais et al, 2005b) and changes in long-term climate (Davi et al, 2006) will also affect European carbon storage.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of literature on estimation of the forest carbon sink and effects of management practices (e.g. Janssens et al 2005;Helin et al 2013;Lundmark et al 2014). Carbon is stored in soil and aboveground biomass, but is released from clear cutting and wood products.…”
Section: Quantitative Methodsmentioning
confidence: 99%